Dreaming Apecar - Leon, Dario (Italy : Redibis Film, 2013)
Caterina is a 45-year-old Italian woman who has been without a job for months and cannot find another one. She accepts work for a career for Gheorghe, an elderly lively Romanian stuck to wheelchair. This experience will change her life.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films